Breve reseña sobre la verdad en el pragmatismo de Charles S. Peirce y William James - Velázquez, Hugo José Francisco (Sapientia, 2019)
Pragmatism is usually thought to constitute a philosophical school whose representatives hold a series of postulates, among which is the thesis that truth is simply identified with what is useful. However, both statements are false, or at least exaggerated, since, on the one hand, pragmatism is a fairly heterogeneous tradition and, on the other hand, the notion of truth within pragmatism implies a complex concept that varies according to each author. This article aims to develop a detailed analysis and confrontation of the conceptions of truth held by Charles S. Peirce and by William James, two of the most important representatives of classical pragmatism. All this in order to partially show that, on the one hand, it is exaggerated to identify the pragmatist conception of truth with what is useful or convenient and, on the other hand, pragmatism should not be conceived as a school or doctrine but as a movement that presents multiple variations.